Bhartatil sthanik swa. Shasan (Maharashtracya vishesh sandarbhasah) - Kulkarni A.N. (Vidya prakashan,Nagpur, 2000)
Sociology
MARATHI
Keywords: Bhartatil sthanik swa. Shasan (Maharashtracya vishesh sandarbhasah); Sociology; Sociology